Methods of Spiral Spring Design - Alexander, B (Aircraft Engineering and Aerospace Technology, 1951)
THE purpose of this article is to present a mathematical treatment which has been found extremely useful in the design of spiral springs since it enables us to determine the physical dimensions of a spiral spring, and also its behaviour when subject to a straining action; i.e. the change of the radius of curvature at any point, change in the number of coils or in the spacing of coils. The following method concerns itself only with the spiral springs whose coils throughout the whole range of deflexion are free, i.e. do not touch one another, and also the springs which become completely solid at the maximum deflexion.